An exploratory research : the factors affecting the choice of industry by entrepreneurs setting up small and medium enterprises (SMEs). - Ang, Tung Xan (2014)
The purpose of this research is to find out factors affecting the choice of industry by local entrepreneurs setting up SMEs and their approaches to strategic planning before and after setting up a venture. The topics touched and scrutinised by local academics had mainly been on the SMEs' roles, their contributions to the Singapore economy and the problems faced by them. As it had been a particular focal point of the Singapore Government in developing a second wing (an external economy), it would be interesting to study the behavioural aspects of entrepreneurs in venturing into new businesses and the reasons affecting their choices.